Analis Hak Kekayaan Intelektual Menjadi Jaminan Pembiayaan Perspektif Ekonomi Syariah - Aufal Marom (Deposisi: Jurnal Publikasi Ilmu Hukum, 2026)
This study examines the legal status of Intellectual Property Rights (IPR) as collateral for financing from the perspective of Islamic economics. Although Law Number 24 of 2019 on the Creative Economy does not explicitly recognize IPR as collateral, its preamble emphasizes that the creative economy generates added value and economic benefits that may serve as financing assets. Consequently, IPR, as an outcome of creative economic activities, may be interpreted as having the potential to function as collateral. This research employs a normative legal method using statutory, conceptual, and Islamic law approaches through the analysis of legislation, fatwas, and relevant legal literature. The findings indicate that under Indonesian positive law, IPR constitutes an intangible asset with measurable economic value, thereby fulfilling the legal requirements to serve as financing collateral. From the perspective of Islamic law, although IPR is not explicitly discussed in classical Islamic legal sources, its protection is consistent with the principle of hifz al-mal (protection of property) within the objectives of Islamic law (maqashid al-sharia). This recognition is reinforced by the Indonesian Council of Ulama (MUI) Fatwa Number 1 of 2003 on Copyright and Fatwa Number 1/MUNAS VII/MUI/5/2005 concerning the Protection of Intellectual Property Rights. Therefore, IPR may be regarded as mal (property) possessing economic value and may legitimately serve as collateral in Sharia financing, provided that it complies with Islamic principles and applicable legal provisions.